The Performance of Primary School Teachers In the Unit of Education Technical Implementation, Banyumanik, Semarang - Afandi, Muhamad; Yustiana, Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
The purpose of this study is mainly to describe the performance of primary school teachers in the unit of education technical implementation in Banyumanik, Semarang. This research was conducted in January- August 2017. The sample of this research is 162 primary school teachers selected by random sampling technique in order to get the same opportunity as sample. The instruments used in this study were the assessment sheets, the Rating Sheet consisted of 64 items of question, and 3 indicators of Primary School Teacher Performance. The results show that each of Implementation of lesson plans is categorized very well (90, 9%), the execution of the learning is 83.4%, assessment of learning is good (82.8%). The Overall performance of primary school teachers is categorized good ( 85,7%). In other words, the primary school teachers of the unit of education technical implementation in Banyumanik Semarang can arrange the lesson plans, carry out learning and teaching process and assess the learning process in elementary school.